COVID-19 infection-induced type one Diabetes Mellitus and Diabetic Ketoacidosis - Amir Hayat , Sohail Siddique , Syed Rehan Shamim, (Journal of Rawalpindi Medical College, 2021)
A 63 year old female patient presented with one week history of reduced appetite, weakness, nausea, polyuria and occasional vomiting on a back ground of recurrent urinary tract infection and hypothyroidism. She appeared lethargic and dehydrated. The arterial blood gas showed a picture of diabetic ketoacidosis (DKA) which was treated according to the protocol. Viral polymerase chain reaction (PCR) for COVID-19 was positive. The diagnosis of new onset type one diabetes made on the basis of specific antibodies test. Computerized Tomography (CT) of abdomen excluded pancreatic cancer as a cause of new onset diabetes. Hence, the patient was labelled as type one diabetes mellitus induced by COVID-19 virus. She was treated accordingly and sent home on insulin. Follow-up appointment was arranged in the diabetes center of the hospital.